Inverted Pendulum Remote Real-time Controller Implemented in Matlab-Simulink and LabView Environments - Mohyla, Jan (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2016)
V této bakalářské práci bude diskutováno vzdálené řízení demonstrováno na rotačním inverzním kyvadle. Hlavním cílem je navrhnout řízení inverzního kyvadla v Simulinku a zajistit komunikaci v reálném čase mezi regulátorem vytvořeném v Simulinku a LabView programem, běžícím na CompactRIO, který bude propojený s fyzickým systémem. Úkol regulátoru je pouze udržet inverzní kyvadlo ve vzpřímené poloze, nikoli vyšvihnutí do vzpřímené polohy (bude provedeno ručně).

This Bachelor’s thesis focuses on the remote control demonstrated on the rotational inverted pendulum. The objective of this project is to design the control of an inverted pendulum in Simulink environment and to develop a real-time communication protocol between the controller created in Simulink and the LabView software running on Com- pactRIO which will be interconnected with a physical system. The role of the controller is to maintain the pendulum upright not to swing the pendulum upright - the pendulum is swung up manually.
Inverted Pendulum Remote Real-time Controller Implemented in Matlab-Simulink and LabView Environments
Keywords: Rotační inverzní kyvadlo; vzdálené řízení; výměna dat mezi Simulinkem a LabView; sys- tém se spožděním; LQR regulátor; Rotary inverted pendulum; remote control; data exchange between Simulink and Lab- View; network control system; system with delay; LQR regulator